COMMUNICATION IN THE FAMILY AND MORAL PLANTING FOR CHILDREN IN THE CITY OF TANGKAHAN - Andi sahputra; Budiman Purba (Universitas Dharmawangsa Medan, 2023)
ABSTRACT Child behavior is a result of the interpretation of communication by parents in the family. The child’s first education comes from within the family, especially from their parents. Good communication in the cultivation of morals for the child will result in good behavior in the early stages. The problem that is presented is communication the how good the cultivation of morals in the outdoors of the city field. Methods of research used are qualitative descriptive, observations, and interviews performed by each child and parents in the family in the field. The results of the research have been obtained that good two-way communication within the family between parents and children can implant morality in the child, the use of good language in communication avoids the child from bad morality. Key Words: Communication In The Famil, Moral Planting For Children